The effectiveness of Photovoice in increasing Self-Esteem and the Career Maturity of Vocational School Students - Hadi, Abdul; Nurbaiti, Anifa Tuzzuhroh; Aryani, Eka (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Photovoice is a participatory research method that places humans, especially those who are marginalized, as active subjects in the process of data collection and analysis. Rather than being passive research objects, photovoice participants are given the opportunity to express their perspectives, experiences, and knowledge through the lens of a camera. The photovoice method places humans as subjects who have valuable knowledge, experiences, and perspectives. By giving them the tools to express themselves, photovoice can produce a deeper understanding of social issues and encourage positive change. The purpose of this study was to see the effectiveness of photovoice on increasing self-esteem and career maturity of vocational high school students in Bantul. The research method used was a quasi-experimental method using a non-equivalent control group design, each experimental group and control group will be given a pretest and post-test. The results obtained in this study are that photovoice is effective in increasing self-esteem and career maturity of vocational high school students. Photovoice adalah sebuah metode penelitian partisipatif yang menempatkan manusia, khususnya mereka yang terpinggirkan, sebagai subjek aktif dalam proses pengumpulan data dan analisis. Alih-alih menjadi objek penelitian yang pasif, peserta photovoice diberikan kesempatan untuk mengungkapkan perspektif, pengalaman, dan pengetahuan mereka melalui lensa kamera. Metode photovoice menempatkan manusia sebagai subjek yang memiliki pengetahuan, pengalaman, dan perspektif yang berharga. Dengan memberikan mereka alat untuk mengungkapkan diri mereka sendiri, photovoice dapat menghasilkan pemahaman yang lebih dalam tentang isu-isu sosial dan mendorong perubahan positif. Tujuan dari penelitian ini adalah melihat keefektifan photovoice terhadap peningkatan harga diri dan kematangan karir peserta didik SMK di Bantul. Metode penelitian yang digunakan adalah kuasi eksperimen dengan menggunakan non equivalent control group design, masing kelompok eksperimen dan kelompok kontrol akan diberi pretest dan posttest. Hasil yang diperoleh dalam penelitian ini adalah photovoice efektif terhadap peningkatan harga diri dan kematangan karir peserta didik SMK.